Legal analysis of recognition of the artificial intelligence as inventor according to patents law in Nicaragua - Romero Guido, Ana Valeria (Scientific journal of social studies, 2022)
Scientific advances in artificial intelligence (AI) are significant. These range from robotics, through medicine to legal science, which is the science that concerns us. This paper be on questions related to patent law, specifically on the possibility that an artificial intelligence system can be recognized as an inventor. For this, artificial intelligence will be described and the legal effects of the inventive capacity of artificial intelligence will be examined and finally the recognition granted by Nicaraguan legislation to the inventive capacity and the right to patent artificial intelligence as a subject of law. To achieve the stated objectives and build scientific knowledge, a methodology has been drawn up according to a theoretical investigation, applying certain methods to generate knowledge from the integration of the analysis of the legal system, concepts, principles, statements and the norm itself.The legal historical method will be applied to learn about the institution and how it has developed over time. It will be opportune to apply the method of comparative law, to learn about the experiences of some countries such as Spain and the United States that are ahead on the subject and have more tradition. Finally, it will be necessary to implement the systemic method, for the study of the parts that make up the Patent law in Nicaragua, to determine if the application of rights protection for artificial intelligence is legally possible.
Keywords: Artificial Intelligence; Patent Law; Inventor; Inventive Ability; Nicaragua